Adiciones, rectificaciones y actualizaciones a “Mariposas de Venezuela” por Théophile Raymond. VI. Satyrinae (Insecta: Lepidoptera: Nymphalidae). / Additions, rectifications, and updating to “Butterflies of Venezuela” by Théophile Raymond. VI. Satyrinae (Insecta: Lepidoptera: Nymphalidae). - Orellana, Andrés (Anartia, 2020)
RESUMEN Se identifican las especies de la subfamilia Satyrinae (Nymphalidae, Lepidoptera) que aparecen en las acuarelas de Théophile Raymond que ilustran su libro “Mariposas de Venezuela” (1982). Se hacen comentarios sobre el autor, su obra y sus ediciones, así como sobre algunas de los taxones mencionados, incluyendo la propuesta de un cambio de status. ABSTRACT The watercolors of the species of the subfamily Satyrinae (Nymphalidae, Lepidoptera) illustrating Théophile Raymond’s “Butterflies of Venezuela” (1982) are identified. Comments are made on the author, his work and the editions of Raymond’s book, as well as some of the taxa mentioned, including the proposal of one change of status.